Study of Gamma-ray Shielding of Two Different Heavy Metals and their Combination for Cs-137 and Co-60 Sources - Eisa, Mohamed E. M.; Ali, M. D. M.; Abuualreish, Mustafa J. (Engineering, Technology & Applied Science Research, 2023)
This article presents data collected by measurements of lead (Pb) and iron (Fe) and their combination as heavy shielding materials. Measurements were performed using gamma photon energies of 662, 1173, and 1332keV for the Cs-137 and Co-60 sources. The theoretical data part was calculated using WinXCom, Phy-X, and Py-MLUBF software packages. Tables and graphs of the photon Mass Attenuation Coefficient (MAC), Linear Attenuation Coefficient (LAC), Half Value Layer (HVL), Tenth Value Layer (TVL) and Mean Free Path (MFP) are presented for both heavy metals and their combination to study the shielding properties experimentally and theoretically. The results will contribute to the ongoing research as a database for future use.